Peningkatan konduktivitas termal oli sintetis sebagai fluida pemindah panas melalui pencampuran serbuk besi - Adian Rahmat; As Natio Lasman; Dwi Rahmalina (University of Muhammadiyah Jakarta, 2022)
Utilization of renewable energy that is specifically sourced from the sun is a good choice to be applied in Indonesia considering the high intensity of the sun and an even supply throughout the year. Utilization of this energy can be focused on solar thermal energy which is produced using solar thermal power. One of the most important parts of solar thermal power is the heat transfer fluid which functions to absorb the heat from the source and transfer it to a thermal load or heat engine. This research focuses on the process of changing the function of heat transfer fluid sourced from synthetic mineral oil. The choice of synthetic mineral oil has many advantages, especially in terms of price and availability. The main problem is the nature of synthetic mineral oil which has low thermal conductivity; thus, improvements are needed to increase thermal conductivity through the addition of sensible materials. Three samples of synthetic oil were prepared, namely oil 10W-30, 10W-40 and 20W-40 and mixed with iron powder in the range of 4 - 6% by mass. The 10W – 40 synthetic oil has the best heat transfer performance due to the low Total Base Number value. The addition of Fe powder (6 wt%) can accelerate the process of absorption and heat dissipation in synthetic lubricant base hybrid fluid. This research also obtains a critical line graph that can be used as a reference in determining the working balance of hybrid fluid in solar thermal system applications.